Fabrication methods of egg polymer matrix and inner banana trunk polymer matrix using injection moulding versus vacuum assisted resin transfer molding process - Nor, Amira Muhammad (Universiti Sains Malaysia, 2017)
Agriculture waste has been one of the concerns in Malaysia, that motivating research to be made in the field of renewability and biodegradable material. This experiment aim is to reuse the waste of natural material that does not give any economic value and adding value to the material. One way to widen the application of natural filler or fiber is by adding it in plastic to create new composite that able to achieve the performance as synthetic fiber or filler. In consequence to that, instead of using synthetic filler in making composite, there is in need for transition to natural filler to help in reducing natural waste and reducing the material cost. This study solely focus on fabricating polymer matrix using natural material which is chicken egg shell and inner banana trunk by using two types of processes which is injection moulding process and vacuum assisted resin transfer molding. Both processes were investigated and evaluated in terms of steps in fabricating and end result such as appearance. Two type specimens were fabricated reinforced each with egg shell and inner banana trunk.